2014
DOI: 10.5713/ajas.2013.13658
|View full text |Cite
|
Sign up to set email alerts
|

Prolificacy and Its Relationship with Age, Body Weight, Parity, Previous Litter Size and Body Linear Type Traits in Meat-type Goats

Abstract: Data on age and body weight at breeding, parity, previous litter size, days open and some descriptive body linear traits from 389 meat-type, prolific Black Bengal goats in Tripura State of India, were collected for 3 and 1/2 years (2007 to 2010) and analyzed using logistic regression model. The objectives of the study were i) to evaluate the effect of age and body weight at breeding, parity, previous litter size and days open on litter size of does; and ii) to investigate if body linear type traits influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…Black Bengal breed is considered an excellent breed for the various reproductive attributes such as high litter size and early maturity (28). Haldar et al (29) have also recently reported 68.39% multiple births in Black Bengal goats, of which 61.70% were twins. High incidence of twin births (56.3%) has been reported in Black Bengal goats in the neighboring country Bangladesh (30).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Black Bengal breed is considered an excellent breed for the various reproductive attributes such as high litter size and early maturity (28). Haldar et al (29) have also recently reported 68.39% multiple births in Black Bengal goats, of which 61.70% were twins. High incidence of twin births (56.3%) has been reported in Black Bengal goats in the neighboring country Bangladesh (30).…”
Section: Resultsmentioning
confidence: 90%
“…Breed-wise and parity-wise least squares means of litter size for different genotypes at A959C, G1189A, and C818T loci of GDF9 gene. Haldar et al (29) who concluded that larger litter size was strongly influenced by higher parity and higher previous litter size in these goats. Similar findings have also been reported in Damascus goats and crossbred native goats in north Mexico (35,36).…”
Section: Resultsmentioning
confidence: 97%
“…In Merino sheep, it was reported that BW is associated with the traits of MUSWT, LMYP, bone weight in carcass (BONE_WT), carcass bone percentage (BONEP), and FATP [36]. In Black Bengal goats, there is a positive relationship between withers height (WH), distance between tuber coxae bones (DTC), BW, and litter size, while physical strength was implicated in an increased likelihood of multiple births in goats bearing multiple fetuses from those bearing a single fetus [59].…”
Section: Markers Associated With Prolificacy Traitsmentioning
confidence: 99%
“…Body size and shape measured objectively could improve selection for growth by enabling the breeder to recognize early maturing and late maturing animals of different sizes (Akpa et al, 2013). Where genetic evaluation has still limited use, identification of some descriptive linear traits may be useful and farmers' friendly tools for selecting goats with desirable characters (Haldar et al, 2014).…”
Section: Resultsmentioning
confidence: 99%